25 Palliative care education in a pandemic. (14th March 2023) - Hayes, J; Rawlinson, F; Stephenson, C; Gallard, S; Johns, E
Abstract : Background: The COVID-19 pandemic and increased home deaths has highlighted the need for rapid, scaleable and cost-effective education on palliative and end of life care for health and social care staff in community settings. Methods: During COVID the Cardiff University MSc in Palliative Medicine team rapidly developed and delivered webinars on end-of-life care aimed at staff managing patients dying at home or in nursing and residential care from COVID, frailty and other conditions. They were delivered through the Zoom digital platform and made interactive by the Q&A facility, chat function and polls. Sessions were free to attendees as part of Cardiff University's 'Civic Mission.' All sessions were recorded and uploaded to a Cardiff University YouTube channel without time restrictions. A second series of webinars with expanded content was funded by Cardiff and Vale University Health Board and delivered by local clinicians. Electronic feedback was collected via Likert scales on content, delivery and organisation. Results: On evaluation, more than 90% of respondents gave scores of 'very good, or 'excellent' for all domains. Data taken 2–4 weeks after the end of series 1 and the more locally targeted series 2 showed means of 182.6 and 89.4 registrations respectively per session, 49.4 and 33.2 live attendees and 126.6 and 38.6 YouTube viewings. However, re-analysis of YouTube data 22 months after completion of series 1 and 7 months after completion of series 2 showed viewings continuing to rise with more than 180 and 100 viewings respectively for the most popular sessions. Discussion and Conclusion: Valuable and interactive education can be produced and delivered efficiently via virtual platforms and at minimal cost. Good quality digital recording of sessions provides an ongoing and sustainable resource that continues to be accessed regularly approaching 2 years after some live events.